2018
DOI: 10.3846/jcem.2018.1646
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Approximate Construction Duration Prediction Model During the Project Planning Phase for General Office Buildings

Abstract: Abstract. Accurate prediction of the construction duration is imperative to the reliable cash flow analysis during the project planning phase when feasibility analysis is carried out. However, lack of information and frequent changes that occur as a result of a negotiation process between the owner and the designer in defining the project scope make it difficult to compute real-time construction duration. Domestic and foreign models for calculating the construction durations cannot be readily applied to comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…In addition, the proposed method estimation error constitutes an improvement above the customized agencies tools whose error was found to be 200% in some studies (Abdel-Raheem et al, 2018). Further, the obtained results are in conformity with the literature finding that prediction of construction duration is more challenging than cost (Pesko et al, 2017, Yeom et al, 2018. This is demonstrated by the results where the error percentages of ensemble duration models are higher than those of ensemble cost models.…”
Section: Testingsupporting
confidence: 85%
“…In addition, the proposed method estimation error constitutes an improvement above the customized agencies tools whose error was found to be 200% in some studies (Abdel-Raheem et al, 2018). Further, the obtained results are in conformity with the literature finding that prediction of construction duration is more challenging than cost (Pesko et al, 2017, Yeom et al, 2018. This is demonstrated by the results where the error percentages of ensemble duration models are higher than those of ensemble cost models.…”
Section: Testingsupporting
confidence: 85%
“…Literature indicates that case studies are necessary for the analysis of the status and problems of calculating construction duration, along with a proposed model utilizing factors affecting the construction duration [51][52][53]. Toor and Ogunlana [6] conducted a case study of international airport construction projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yeom [53] conducted a case study to develop a construction estimation model using multiple linear regression during the project planning phase for office buildings in Korea. Their findings showed that the average construction duration was dependent on various factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…duration. These additional variables have included quantitative and qualitative factors as scope related (Le-Hoai et al , 2013; Hoffman, 2005; Yeom et al , 2018). This study is delimited to project scope factor, which includes, construction cost, gross floor area, number of floors, average floor area, project type and cost level factors as potential predictive variables for time prediction model as these factors are widely recognized by previous studies and proved to be identifiable during the early phase.…”
Section: Literature Reviewmentioning
confidence: 99%